Effect of High Frequency Repetitive Transcranial Magnetic Stimulation Combined with Voice Training on Voice Function of Patients with Parkinson's Disease - WANG Xiaowen; ZHU Qingqing; CHEN Yan; QIAN Hong; YUAN Haixin; ZHAO Gang; LIU Jie; ZHANG Fengjiao (康复学报)
ObjectiveTo observe the effect of high frequency repetitive transcranial magnetic stimulation (rTMS) combined with voice training on voice function of patients with Parkinson's disease (PD).MethodsA total of 30 patients of Parkinson's disease with voice disorder were treated in the department of rehabilitation medicine and the department of geriatrics of Shanghai Fifth Rehabilitation Hospital from October 2019 to July 2021, which were randomly divided into the control group and the observation group according to Excel RAND function, with 15 cases in each group. The control group were treated with routine anti PD drugs and routine voice training, including abdominal breathing training, respiratory and vocal coordination training, breathing support ability training, voice real-time stress therapy, tonal training,vocal cord relaxation training, tone quality training,resonance relaxation training, etc.The training time was 40 minutes a time, once a day, continuous training for 30 days.The observation group received high-frequency rTMS stimulation on the basis of the control group. High frequency (5 Hz) rTMS was used to stimulate bilateral primary motor cortex (M1 area). The stimulation time was 10 minutes, 20 minutes a time,once a day, continuous training for 30 days. Before treatment, after treatment (after treatment for 30 days) and follow-up (30 days after the end of treatment), voice function detection and correction instrument, voice function detection and correction instrument were used to detect voice function under the framework of ICF, mainly including voice production index [(maximum phonation time, MPT), (maximum counting ability, cMCA), (fundamental frequency, F0), (contact quotient, CQ), (contact quotient perturbation, CQP), (fundamental frequency tremor, F0t),(frequency band energy concentration rate，Ec)] and voice quality index[Jitter, Shimmer, (normalized noise energy, NNE), F2/u/,F2/i/]. Voice handicap index (VHI) questionnaire were used to evaluate the subjective feelings of patients with voice disorders.ResultsBefore treatment, there were no significant difference in MPT, cMCA, F0t, Ec, F0, CQ, CQP, Jitter, Shimmer, NNE, F2/i/, F2/u/, VHI between the two groups (P>0.05). Compared with before treatment, MPT,cMCA, F0t, Ec and F2/i/ of the two groups after treatment were significantly increased, F0, NNE and VHI score of the two groups after treatment were significantly decreased (P<0.05); MPT, cMCA, F0t, Ec, F2/i/ score of the observation group follow-up were significantly increased (P<0.05),and the scores of F0, NNE and VHI score of the observation group follow-up were significantly decreased (P<0.05). Compared with after treatment, MPT and cMCA of the observation group follow-up were significantly decreased (P<0.05). Compared with the control group at the same time, MPT, cMCA, F0t, Ec, F2/i/ of the observation group after treatment and follow-up were significantly increased, and the scores of CQP, NNE and VHI score were significantly decreased (P<0.05).ConclusionHigh frequency rTMS combined voice training can improve the respiratory support ability, the coordination ability of breathing and vocalization, the regularity of vocal cord closure, the forward movement ability of tongue in PD patients; reduce vocal cord tremor, attenuation of harmonic energy during vocal cord vibration,breath sound and self subjective feeling of voice disorder, and its long-term effect is also good, which is worthy of clinical promotion.